Epidemiology of perioperative cardiac arrest and mortality in Brazil: a systematic review - Braz,Leandro Gobbo (2020)
Abstract Background and objectives: The perioperative cardiac arrest (CA) and mortality rates in Brazil, a developing country, are higher than in developed countries. The hypothesis of this review was that knowledge of the epidemiology of perioperative CA and mortality in Brazil enables the comparison with developed countries. The systematic review aimed to verify, in studies conducted in Brazil, the epidemiology of perioperative CA and mortality. Method and results: A search strategy was carried out on different databases (PubMed, EMBASE, SciELO and LILACS) to identify observational studies that reported perioperative CA and/or mortality up to 48 hours postoperatively in Brazil. The primary outcomes were data on epidemiology of perioperative CA and mortality. In 8 Brazilian studies, there was a higher occurrence of perioperative CA and mortality in males; in extremes of age; in patients in worse physical status according to the American Society of Anesthesiologists (ASA); in emergency surgeries; in general anesthesia; and in cardiac, thoracic, vascular, abdominal and neurological surgeries. The patient's disease/condition was the main triggering factor, with sepsis and trauma as the main causes. Conclusions: The epidemiology of both perioperative CA and mortality events reported in Brazilian studies does not show important differences and, in general, is similar to studies in developed countries. However, sepsis represents one of the major causes of perioperative CA and mortality in Brazilian studies, contrasting with studies in developed countries in which sepsis is a secondary cause.